2014
DOI: 10.1021/am5026159
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Carrier Trapping of a Metal-Doped Titanium Dioxide Semiconductor Revealed by Femtosecond Transient Absorption Spectroscopy

Abstract: We explored for the first time the ultrafast carrier trapping of a metal-doped titanium dioxide (TiO2) semiconductor using broadband transient absorption (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 42 publications
(87 reference statements)
4
44
0
Order By: Relevance
“…Ultrafast spectroscopy was also applied to track photoexcited charge carriers in doped TiO2 [37][38][39][40][41][42]. Ikeda et al observed a second-order kinetics due to electron-hole recombination, the rate constant of which increases with increasing dopant concentration [42].…”
Section: Introductionmentioning
confidence: 99%
“…Ultrafast spectroscopy was also applied to track photoexcited charge carriers in doped TiO2 [37][38][39][40][41][42]. Ikeda et al observed a second-order kinetics due to electron-hole recombination, the rate constant of which increases with increasing dopant concentration [42].…”
Section: Introductionmentioning
confidence: 99%
“…The fast component is linked to the trapping of the electron by the defect state located immediately below the conduction band, whereas the second time component is attributed to carrier trapping by deep-level trap states located near the center of the bandgap. 49 It is worth mentioning here that to understand the precise location of the intra-band defect states, we must turn to high-level theoretical investigations, which are beyond the scope of this study. After ZnS shelling, it is observed that for CIS and CISSe, the fast component still remains but with less amplitude, and the other component (with the hundreds of picosecond time constant before shelling) is almost completely removed.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The kinetic traces can be fitted bi‐exponentially with less than 200 fs and ps time constants. The fs and ps time components can be assigned to surface and deep trapped states, respectively . Interestingly, upon increasing the thickness of the TiO 2 , the lifetime of the carriers decreases significantly.…”
Section: Resultsmentioning
confidence: 98%